2015
DOI: 10.1039/c5ra01455g
|View full text |Cite
|
Sign up to set email alerts
|

Control of manganese dioxide crystallographic structure in the redox reaction between graphene and permanganate ions and their electrochemical performance

Abstract: MnO2 crystallographic structure was well controlled in the redox reaction between graphene and permanganate ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 38 publications
0
15
1
Order By: Relevance
“…The cyclic voltammogram, having two peaks during discharge and having a peak with shoulder during charge, exhibits typical characteristics of the electrochemical insertion/extraction of Zn 2+ ions in MnO 2 structure 12,13,3941 . These results with two peaks during discharge may be more clearly described by the two-step reaction of Zn 2+ ion insertion in electrochemical reaction 12,38 and spinel-type ZnMn 2 O 4 transformation 33 . In the following scan cycles, the peaks at 1.37 V for δ-MnO 2 and at 1.38 for MNG increase gradually during discharge indicating an activation process 38 .…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…The cyclic voltammogram, having two peaks during discharge and having a peak with shoulder during charge, exhibits typical characteristics of the electrochemical insertion/extraction of Zn 2+ ions in MnO 2 structure 12,13,3941 . These results with two peaks during discharge may be more clearly described by the two-step reaction of Zn 2+ ion insertion in electrochemical reaction 12,38 and spinel-type ZnMn 2 O 4 transformation 33 . In the following scan cycles, the peaks at 1.37 V for δ-MnO 2 and at 1.38 for MNG increase gradually during discharge indicating an activation process 38 .…”
Section: Resultsmentioning
confidence: 71%
“…4(a), a dominating pair of redox peaks exhibits increasing currents when the sweep rates increase, which do not display rectangular-shape and symmetrical voltammograms even at high scan rates, compared to MnO 2 /activated carbon composite for supercapacitors 32 . It is noted that the MNG electrode does not present the capacitive behavior of the electrode 33,34 . The capacitive effect is characterized by analyzing the cyclic voltammetry data at different sweep rates as in Eq.…”
Section: Resultsmentioning
confidence: 99%
“…While XPS is usually a powerful tool to investigate the chemical composition of amorphous thin films, the interpretation of XPS data is difficult in the case of MnO x due to the sheer number of structures, morphologies, and shapes that exist for each corresponding oxidation state [48–50] . To understand the efficiency towards water splitting, it is especially important for mixed manganese oxides to probe the exact chemical composition because the mix can contain up to three different manganese valences in various concentrations [35,51] .…”
Section: Resultsmentioning
confidence: 99%
“…The results show that a weak diffraction peak can be mainly attributed to the prepared sample, which indicates low crystallinity. Nevertheless, it can still be clearly found that the diffraction peaks at 2θ values of 37.2° and 66.8° were due to the (111) and (020) crystal planes of the birnessite-type MnO 2 (JCPDS 18-0802, Joint Committee on Powder Diffraction Standards (JCPDs), Newtown Square, PA, USA) [ 27 ] and that the peak width of the peak intensity was not strong. It is revealed that the MnO 2 material prepared by the SILAR method was not highly crystalline and that the crystallinity was not perfect.…”
Section: Resultsmentioning
confidence: 99%